SRATEGI PENGUSAHA BATIK TULIS LASEM DALAM MENGEMBANGAN USAHA DI ERA DISRUPTION - Roziqin, Ali; Retnandari, Nunuk Dwi (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2021)
Rembang Regency not only has abundant marine and coastal resources, but also the potential of creative industries. One of them is Lasem batik. Batik tulis Lasem can be considered and recognized as an icon local pride of the Rembang community. Although Pekalongan, Surakarta (Solo) and Yogyakarta are the places which batik aesthetically well-known by public the most, Batik tulis Lasem has also uniqueness that makes it uncanny due to its distinctive colour and, patterns. Currently we are living in the era of disruption, whereas a condition that occurs social change due to technology revolution and innovation, including changes in business model, consumer behavior, and the market demand. Therefore, this article, the author wants to explore the strategies which are carried out by batik entrepreneurs in business development during the disruption era. In this study, The researchers use descriptive qualitative methods by collecting primary and secondary data. The result is that Lasem batik entrepreneurs have varied strategies depending on the ability of the entrepreneur's resources and the scale of the business they have.